Talking about Europe: Exploring 70 years of news archives - Enrico Bergamini; Emmanuel Mourlon-Druol (Bruegel, 2021)
This paper quantitatively explores news coverage on the subject of "Europe" in three different countries and three newspapers: France (Le Monde), Italy (La Stampa) and Germany (Der Spiegel). We collected and organised large web-scraped datasets covering the period 1945 to 2019. After ensuring the quality of the archives, we identified articles referring to "European" news while leaving aside national and other non-European news, based on a mix of keyword matching, large-scale natural language processing and topic identification on the full text of news articles. Once articles were classified and datasets labelled, we performed a time-series analysis, detecting salient events in European history, across France, Germany and Italy. We analysed these events in light of the evolution of European cooperation and integration since 1945. We found that the most important events in post-war European history are easily identifiable in the archives and that European issues have gathered substantially greater attention since the early 1990s.
Keywords: 330